2018
DOI: 10.1155/2018/7382946
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutrition during Early Pregnancy and Cardiometabolic Status of Neonates at Birth

Abstract: Objective To explore the impact of maternal body weight on maternal nutrition and micronutrient status in early pregnancy and potential impact on metabolic status in newborns. Methodology The EU FP7 project GIFTS was conducted from Jan 2012 to May 2014. Demographic details and anthropometric measurements of women in the first trimester of pregnancy were obtained. Blood samples were collected for OGTT, insulin, lipid profile, serum folate, ferritin, vitamin D, vitamin B12, and red cell folate. Newborn anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Our data showed a high prevalence of vitamin D deficiency and insufficiency in pregnant women in early pregnancy. Studies in Pakistan with identical definition for vitamin D deficiency with similar inclusion criteria had shown similar results [15, 32]. Similar findings were also observed in other studies conducted in Bangladesh [33] and India [34].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our data showed a high prevalence of vitamin D deficiency and insufficiency in pregnant women in early pregnancy. Studies in Pakistan with identical definition for vitamin D deficiency with similar inclusion criteria had shown similar results [15, 32]. Similar findings were also observed in other studies conducted in Bangladesh [33] and India [34].…”
Section: Discussionsupporting
confidence: 83%
“…This is one of several sub studies of a prospective multi-center EU FP7 project GIFTS (Genomic and lifestyle predictors of fetal outcome relevant to diabetes and obesity and their relevance to prevention strategies in South Asian peoples) project conducted from April 2011 and June 2012 in Dhaka, Bangladesh. Other GIFTS studies included analysis of other populations in Pakistan [15] and Bangladeshi’s in the UK, a micronutrient intervention study in pregnancy in Dhaka (ISRCTN Number: 83599025), genomic predictors of birthweight and gestational diabetes (GDM) in South Asian populations, analysis of body composition in Bangladeshi children aged 2–4 in whose mothers were exposed to a community mobilization program [16], studies in GDM [1719] and social and cultural influences of South Asian women during pregnancy [20].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ID may also be a marker for other nutritional issues. In a study from Pakistan, underweight women in early pregnancy had lower serum ferritin concentrations than either normal body weight or overweight mothers [75].…”
Section: Impact Of Id During Pregnancymentioning
confidence: 90%
“…In children and adolescents, increase in BMI 13 and IR 14 have been associated with low B12 levels. Furthermore, studies in early pregnancy have focussed on association between lower maternal micronutrient status (B12, folate, iron) with pre-pregnancy overweight and obesity in mothers 15,16,17 , with lower micronutrients in low-birth weight infants 18 and with higher BMI and heart rate in children at age 5-6 19 . Our in vitro studies have shown that B12 deficiency in adipocytes altered DNA methylation levels 2 of the transcription factors of lipid regulation 2 and the adipose derived miRNAs targeting IR 3 thereby suggesting that B12 deficiency dysregulates epigenetic mechanisms.…”
Section: Sdmentioning
confidence: 99%